Perceptions of campaign donors and their impact on judgments of judicial fairness - Nunez, Narina (Psychology, crime & law, 2022)
Perceptions of judicial fairness for elected state judges were examined across a series of studies. Of particular interest was how campaign donations and types of cases affect perceptions that judges could be fair. In Study 1, participants (N = 120) rated the political orientation of 14 groups or companies known to provide campaign contributions and rated how fair judges could be if they received donations from these entities. In Study 2, participants read about a judge who received donations from a liberal or conservative political action committee (N = 190) or corporation (N = 188). Study 3 (N = 809) tested whether judicial recusal in conflicted cases could repair perceptions of judicial fairness. Individual differences in participant political orientation were also examined. Across all studies, participants rated judges as less fair when they received donations during their campaigns and later heard cases that were clearly related to donors’ interests. Significant interactions between participant and donor political orientation were found. Generally, liberal participants thought judges would be less fair when donors were conservative, and conservative participants thought judges would be less fair when donors were liberal. Finally, judicial recusal led to higher future fairness ratings.